Mali Africa RISING: Farm Characterization Survey - Wageningen University and Research; International Crops Research Institute for the Semi-Arid Tropics (International Food Policy Research Institute, 2015)
This data study contains data on the farm characterization survey conducted in the villages of Sirakele, Sibirila, and Dieba. Project title: Africa RISING- Research in Sustainable Intensification of Cereal-Based Farming Systems in the Guinea-Sudan-Savanna of West Africa Project abstract: Sustainable intensification of mixed crop livestock systems is a key pathway towards better food security, improved livelihoods and a healthy environment. As part of the US government?s Feed the Future initiative to address hunger and food security issues in sub-Saharan Africa, the US Agency for International Development (USAID) is supporting three multi-stakeholder agricultural research projects to sustainably intensify key African farming systems. Project website: http://africa-rising.net